The Influence of Cell Source and Donor Age on the Tenogenic Potential and Chemokine Secretion of Human Mesenchymal Stromal Cells - Weronika Zarychta-Wiśniewska; Anna Burdzińska; Katarzyna Zielniok; Marta Koblowska; Kamila Gala; Piotr Pędzisz; Roksana Iwanicka- Nowicka; Anna Fogtman; Aleksandra Aksamit; Agnieszka Kulesza; Aleksandra Zołocińska; Leszek Pączek (Hindawi Limited, 2019)
Background. Cellular therapy is proposed for tendinopathy treatment. Bone marrow- (BM-MSC) and adipose tissue- (ASC) derived mesenchymal stromal cells are candidate populations for such a therapy. The first aim of the study was to compare human BM-MSCs and ASCs for their basal expression of factors associated with tenogenesis as well as chemotaxis. The additional aim was to evaluate if the donor age influences these features. Methods. Cells were isolated from 24 human donors, 8 for each group: hASC, hBM-MSC Y (age≤45), and hBM-MSC A (age>45). The microarray analysis was performed on RNA isolated from hASC and hBM-MSC A cells. Based on microarray results, 8 factors were chosen for further evaluation. Two genes were additionally included in the analysis: SCLERAXIS and PPARγ. All these 10 factors were tested for gene expression by the qRT-PCR method, and all except of RUNX2 were additionally evaluated for protein expression or secretion. Results. Microarray analysis showed over 1,400 genes with a significantly different expression between hASC and hBM-MSC groups. Eight of these genes were selected for further analysis: CXCL6, CXCL12, CXCL16, TGF-β2, SMAD3, COLLAGEN 14A1, MOHAWK, and RUNX2. In the subsequent qRT-PCR analysis, hBM-MSCs showed a significantly higher expression than did hASCs in following genes: CXCL12, CXCL16, TGF-β2, SMAD3, COLLAGEN 14A1, and SCLERAXIS (p<0.05, regardless of BM donor age). In the case of CXCL12, the difference between hASC and hBM-MSC was significant only for younger BM donors, whereas for COLLAGEN 14A1-only for elder BM donors. PPARγ displayed a higher expression in hASCs compared to hBM-MSCs. In regard to CXCL6, MOHAWK, and RUNX2 gene expression, no statistically significant differences between groups were observed. Conclusions. In the context of cell-based therapy for tendinopathies, bone marrow appears to be a more attractive source of MSCs than does adipose tissue. The age of cell donors seems to be less important than cell source, although cells from elder donors show slightly higher basal tenogenic potential than do cells from younger donors.